Teologi Inklusif untuk Membangun Kerukunan (Analisis Teks Tutur Jatiswara) - I Komang Suastika Arimbawa; Putu Ayu Septiari Dewi (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2020)
Harmony can be interpreted as a living and living condition that reflects an atmosphere of peace, order, peace, prosperity, respect, respect, price respect, tolerance, mutual cooperation in accordance with religious teachings. Harmony that adheres to the teachings of each religion can make every group among fellow human beings who have different beliefs as an open group (inclusive). Regarding this reality, in the text of Tutur Jatiswara there is an inclusive theological concept that can be a